If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3v + -4) = 51 Reorder the terms: 3(-4 + 3v) = 51 (-4 * 3 + 3v * 3) = 51 (-12 + 9v) = 51 Solving -12 + 9v = 51 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9v = 51 + 12 Combine like terms: -12 + 12 = 0 0 + 9v = 51 + 12 9v = 51 + 12 Combine like terms: 51 + 12 = 63 9v = 63 Divide each side by '9'. v = 7 Simplifying v = 7
| 1.25(s+72)=250 | | (5u-7)(2+u)=0 | | .4(2-q)=0.2(q+7) | | 3(5)+5x=9 | | 35-x=4x | | y+7/9=8/5 | | Y=5/2x+20 | | x^2-1.375x=7 | | x-35=4x | | (4x-9)/(7x^2+9x) | | -4-(5-3p)= | | x-3/4-2=x-2/3 | | 5.3x+4=4.3x | | 34=5x+16x^2 | | 6x-(-3x+9)=(x-7)-4(9x-9) | | (4x-9)/(7x^2+9) | | 5[x]=45 | | 5n+1=5(n-1) | | 8(k+11)-6k=9 | | 3u+4=22 | | 16x^2+5x=0 | | 7x+21=2x+56 | | 20y^2-15y^3= | | 1/4(x-3)=1/3(x-2) | | f(x)=5-.2x | | c/8+230/8=200 | | 22/1 | | 5r^2-16r+12= | | -5y-9=4y+2 | | 3k+34=4(6+3k)+1 | | -6-(-2n)=3-6+5 | | 15-2x=-19 |